Improved Glass Transition Temperature towards Thermal Stability via Thiols Solvent Additive versus DIO in Polymer Solar Cells. Issue 20 (25th August 2017) - Yin, Jingping; Zhou, Weihua; Zhang, Lin; Xie, Yuanpeng; Yu, Zoukangning; Shao, Jun; Ma, Wei; Zeng, Jianrong; Chen, Yiwang
Abstract: The halogen‐free solvent additive, 1, 4‐butanedithiol (BT) has been incorporated into PTB7‐Th:PC71 BM, leading to higher power conversion efficiency (PCE) value as well as substantially enhanced thermal stability, as compared with the traditional 1, 8‐diiodooctane (DIO) additive. More importantly, the improved thermal stability after processing with BT contributes to a higher glass transition temperature ( T g ) of PTB7‐Th, as determined by dynamic mechanical analysis. After thermal annealing at 130 °C in nitrogen atmosphere for 30 min, the PCE of the specimen processed with BT reduces from 9.3% to 7.1%, approaching to 80% of its original value. In contrast, the PCE of specimens processed with DIO seriously depresses from 8.3% to 3.8%. These findings demonstrate that smart utilization of low‐boiling‐point solvent additive is an effective and practical strategy to overcome thermal instability of organic solar cells via enhancing the T g of donor polymer. Abstract : The halogen‐free solvent additive of 1, 4‐butanedithiols (BT) can improve power conversion efficiency and substantially enhance thermal stability of PTB7‐Th:PC71 BM, as compared with the traditional 1, 8‐diiodooctane additive. More importantly, the improved thermal stability after processing with BT contributes to higher glass transition temperature ( T g ) of PTB7‐Th, as determined by dynamic mechanical analysis.